Physicochemical and morphological characteristics of potato pectin with in‐situ acid‐induced gelation. Issue 9 (21st August 2022) - Hu, Qiang; Shi, Bingyan; Dong, Nan; Yu, Xiaoyan; Xiao, Chunhua; Lei, Zunguo; Li, Fei; Ren, Tingyuan; Liu, Jia
Abstract : Abstract: Pectin in the potato cell wall plays an important role in strengthening connections of intercellular junctions during thermal processing through in‐situ acid‐induced gelation (in‐situ acid‐induced gelation [AIG]). Thus, the variation in the physicochemical and structural characteristics of potato pectin with in‐situ AIG was focused in this study. The intra‐ and intermolecular hydrogen bonding among (d ‐galacturonic acid) GalA units around 3400 cm –1 (absorbance intensity was increased from 50.9 to 70.7) in Fourier transform infrared spectra were enhanced in the pectin with in‐situ AIG. The crystallinity of pectin with in‐situ AIG increased from 4.02% to 36.63%. Atomic force microscopy revealed that pectin with in‐situ AIG was made up of wide linear strands with the length from 0.5 to 4.6 µm. Thermogravimetric and rheological analysis showed that the structure of potato pectin was more stable and resistant to heat processing after in‐situ AIG. These observations proved that the complex structure of potato pectin with in‐situ AIG linked with its thermal stability. Practical Application: In‐situ gelated pectin in the intercellular space caused a helpful structure modification of vegetable to maintain its hardness with heat process. This study will provide novel insights into the physicochemical properties of in‐situ gelated pectin in the potato cell and useful knowledge on the behavior of pectin during the preparation of potato products.